Study of Pt and Rh based supported catalysts modified with tetrabutyltin for the selective hydrogenation of 4-methoxyacetophenone - Vetere, Virginia (2007)
Catalysts based on Pt and Rh modified with Sn(C4H9)4 were studied in the hydrogenation of 4-methoxyacetophenone. The selectivity to 1-(4-methoxyphenyl)ethanol was close to 100% at Sn/(Pt,Rh) = 1.0, however the catalytic activity decreased drastically. With respect to the balance between activity and selectivity the catalyst PtSnOM (Sn/Pt=0.4) showed the best performance.